SYMBOLIC MEANINGS AND METHODS OF EMBROIDERY - S.A. Rakhimkulova; U.S. Rakhmatullayeva; S.A.Abrayeva (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
Symbolic meanings and methods of application of patterns used in embroidery. Embroidery is a unique source for the study of ornament, which has played an important role in the history of Central Asian art. Its most archeological part is geometric patterns: circles, whirlpool flowers, triangles, rhombuses, straight and wavy lines, faceted elements that traditionally have the meaning of cosmological symbols.